2022
DOI: 10.1002/admi.202201757
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Coatings for Endotracheal Tubes Probed on An Ex Vivo Extubation Setup

Abstract: Endotracheal intubation is indispensable in modern healthcare but typically entails two complications for the treated patients: biofouling‐induced infections and friction‐associated damage to the tissue. Coatings on the endotracheal tubes (ETT) may mitigate those problems, but they require a well‐defined testing method to assess their functionality. Here, such a testing setup is presented, which allows for conducting ex vivo extubation experiments in a reproducible manner. With this setup, different coating st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Of course, not only a colonization by eukaryotic and prokaryotic cells but also an adsorption of molecules onto the ETT surface can alter the surface properties of the tube and thus affect its behavior. In previous studies, we observed that mucin coatings can also very efficiently reduce lipid deposition events onto medical devices such as contact lenses and ETTs, 7,13 and we reproduced this behavior here (Fig. 2f and ESI, section S8†).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Of course, not only a colonization by eukaryotic and prokaryotic cells but also an adsorption of molecules onto the ETT surface can alter the surface properties of the tube and thus affect its behavior. In previous studies, we observed that mucin coatings can also very efficiently reduce lipid deposition events onto medical devices such as contact lenses and ETTs, 7,13 and we reproduced this behavior here (Fig. 2f and ESI, section S8†).…”
Section: Resultssupporting
confidence: 85%
“…12 In recent work, we introduced a setup that enabled us to perform ex vivo extubation tests on porcine tracheas, and we employed this setup to assess the functionality of mucin coatings generated on endotracheal tubes (ETTs). 13 Such mucins are large glycoproteins, which are physiologically present on all wet epithelia of mammalians. Here, they are responsible for a range of important tasks such as providing tissue hydration, lubricity, as well as anti-viral and anti-bacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, dopamine molecules can stably attach to a broad range of materials, which renders dopamine‐based intermediate layers a versatile tool to generate macromolecular coatings. [ 39–41 ] The FTIR spectra acquired from such modified surfaces confirm that this coating process was successful. However, owing to the polysaccharidic nature of both cellulose and pectin, differences in the FTIR spectra are restricted to specific areas.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, polymer coatings have been applied for reducing the friction between implants and tissues. However, the biopolymers anchored to the surface have to be large enough (ideally, in the MDa range) to achieve a good lubrication function, and this limits the biopolymer options . With those aspects in mind, multilayer coatings may offer a promising tool for surface lubrication without the need to develop new macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…However, the biopolymers anchored to the surface have to be large enough (ideally, in the MDa range) to achieve a good lubrication function, and this limits the biopolymer options. 38 With those aspects in mind, multilayer coatings may offer a promising tool for surface lubrication without the need to develop new macromolecules. Additionally, given the extensive number of studies on polyelectrolyte multilayers as drug reservoirs, 39−41 the potential of PDA-biopolymer multilayers for applications in drug delivery is high as well.…”
Section: ■ Introductionmentioning
confidence: 99%